Copts in modernity proceedings of the 5th International Symposium of Coptic Studies, Melbourne, 13-16 July 2018 - Agaiby, Elizabeth; Swanson, Mark N.; Doorn-Harder, Pieternella van 1956- (Brill, 2021)
History -- Education, leadership, and service -- Identity and material culture
Keywords: Geschichte 1800-2000; Koptische Kirche; Coptic Church / History / Congresses; Konferenzschrift -- 13.07.2018-16.07.2018 -- Melbourne